The role of neuro-supportive substances of natural origin in neurological conditions—A literature-based formulators' perspective - van Brummelen, Roy; van Brummelen, Anna C. (Frontiers in Neurology, 2025)
Products of natural origin are seldom tested up to a point of full acceptance, mainly due to a lack of financial viability for commercialization. Yet many come with a rich history of use and proof of concept testing. We investigated literature regarding the possible role and function of the best known of these nutraceuticals in relationship to three neurological conditions i.e. stroke, Alzheimer's - (AD) and Parkinson's disease (PD), and their potential as supportive therapies. Current studies suggest that citicoline has a neuroprotective effect in ischemic conditions, playing a role in the restoration of the barrier function of endothelial cells, activating repair mechanisms and possibly decreasing ischemic lesion size in stroke, as well as increasing dopamine availability in PD. Citicoline was also demonstrated to increase the levels of sirtuin 1 (SIRT1), thus reducing inflammation—leading to improved cognitive status and a better quality of life in cognitive impairment. N-Acetylcysteine (NAC) shows pro-cognitive effects, increasing glutathione (GSH) levels that are decreased in AD and PD patients, possibly decreasing neuroinflammation. Mechanistic studies indicate the potential neuroprotective and neurorestorative effects of resveratrol by its anti-inflammatory and anti-apoptotic activity, also increasing SIRT1 levels and promoting the outgrowth of neurite protrusions and synaptogenesis. Curcumin's anti-inflammatory effects via inhibition of interleukin 1 (IL-1) and tumor necrosis factor-alpha (TNF-alpha) can potentially delay progression of PD. Some nutraceuticals, e.g., citicoline, show synergism in combination with current therapies. We propose a renewed, risk-benefit approach for inclusion of the investigated nutraceuticals with limited indications in certain neurological treatment regimens.